Evaluating the Effectivieness of Principal Management in Improving Elementary School Quality: A Systematic Literature Review - Selvi Wulandari; Rosida Marasabessy; Risna Srinawati; Muhammad Rafid Barmawi; Ariestha Widyastuty Bustan (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to evaluate the effectiveness of principal management in improving the quality of elementary schools by synthesizing and critically examining evidence from previous research. The study emphasizes an evaluative perspective to identify which leadership strategies contribute most significantly to school quality improvement. Methodology: This study employs a systematic literature review (SLR) using PRISMA guidelines. A total of 13 relevant articles published in reputable journals were selected based on predefined inclusion and exclusion criteria. The data were analyzed using a thematic evaluative synthesis approach to assess the effectiveness of various principal management practices. Main Findings: The results indicate that instructional leadership, data-driven management, and collaborative leadership approaches demonstrate the highest effectiveness in enhancing teacher performance, learning quality, and student outcomes. In contrast, administrative and routine managerial practices show limited impact when implemented without integration with instructional and transformational strategies. The findings also reveal that the majority of previous studies are dominated by qualitative and context-specific approaches, limiting generalizability and the strength of causal conclusions. Novelty/Originality of this study: This study contributes to the literature by shifting the focus from descriptive synthesis to an evaluative analysis of principal management effectiveness. It provides a comprehensive evaluation framework that integrates leadership practices with school quality outcomes. The study also offers practical implications for educational evaluation and policy by emphasizing the importance of evidence-based leadership and continuous performance assessment in improving elementary school quality.